Comparison of Motor Ability of Bachelor HPE Students in Makawanpur Multiple Campus and Ramshwaroop Ramsagar Multiple Campus - Shrestha, Mitra Lal (Prajnik Bimarsha प्राज्ञिक विमर्श, 2025)
The primary purpose of this paper was to study the status of motor ability of girl students from Makawanpur Multiple Campus, Hetauda and Ramshwaroop Ramsagar Multiple Campus, Janakpur through 50 yard dash, shot put and standing broad jump test . The 30 girl students of Makawanpur Multiple Campus and 30 girl students of Ramshwaroop Ramsagar Multiple Campus were selected as participants for the research paper . The participants were selected from two campuses of 60 students through purposive sampling . Differences in motor ability were evident between the girl students of both campuses . The girl students from Makawanpur Multiple Campus, Hetauda demonstrated the better level of performance than the girl students from Ramshwaroop Ramsagar Multiple Campus, Janakpur in 50 yard dash, shot put and standing broad jump test . The study found mean score of girl students from Makawanpur Multiple Campus was better than Ramshwaroop Ramsagar Multiple Campus, Janakpur . It was found that in statistical calculation of z-test, there was a significant difference of motor ability between the girl students of the campuses. Keywords : Athletics, games, motor ability, performance, sports, physical activities.